KEYNES, WICKSELL Y UN CONCEPTO DE INTERÉS MAL ENTENDIDO - MORALES, DANIEL JOSÉ GALLEGO; NEIRA, MIGUEL ÁNGEL ALONSO; ANIA, ALBERTO ROMERO (REVISTA PROCESOS DE MERCADO, 2025)
This article concludes the examination of the concept of the interest rate in John Maynard Keynes’s economic theory, continuing the line of research on the author. On this occasion, we focus on the specific concept as presented in his two main works, tracing the concrete differences between their respective notions of interest and analyzing the extent to which Knut Wicksell influenced them. We will see that Keynes did not fully understand it correctly, and this misunderstanding, carried forward by the British economist, shaped a particular way of interpreting the economic environment that had a direct impact on The General Theory.